2006
DOI: 10.1086/498292
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Type Ia Supernovae at High Redshift

Abstract: We derive the rates of Type Ia supernovae (SNe Ia) over a wide range of redshifts using a complete sample from the IfA Deep Survey. This sample of more than 100 SNe Ia is the largest set ever collected from a single survey and therefore uniquely powerful for a detailed supernova rate (SNR) calculation. Measurements of the SNR as a function of cosmological time offer a glimpse into the relationship between the star formation rate (SFR) and Type Ia SNR and may provide evidence for the progenitor pathway. We obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
4

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(123 citation statements)
references
References 45 publications
6
113
4
Order By: Relevance
“…The largest disagreement between published rates in Figure 10 (and in the literature as far as we know) is that between the rates at z = 0.55 of Pain et al (2002) and Barris & Tonry (2006). We point out that Barris & Tonry (2006) is a re-analysis of the data from Tonry et al (2003), which reported a rate that agrees with Pain et al (2002).…”
Section: Contaminationmentioning
confidence: 59%
See 4 more Smart Citations
“…The largest disagreement between published rates in Figure 10 (and in the literature as far as we know) is that between the rates at z = 0.55 of Pain et al (2002) and Barris & Tonry (2006). We point out that Barris & Tonry (2006) is a re-analysis of the data from Tonry et al (2003), which reported a rate that agrees with Pain et al (2002).…”
Section: Contaminationmentioning
confidence: 59%
“…We find that the single Gaussian model fit to the Dahlen et al (2004) data consistently over-predicts the rates near and below z = 0.5. In particular, the rate from Barris & Tonry (2006) at z = 0.25 is more than 1σ below this model.…”
Section: The Two-component Modelmentioning
confidence: 67%
See 3 more Smart Citations